A functional trait-based approach to disentangle trawling disturbance on bentho-demersal assemblage composition: Evidence from a heavily exploited fishing ground (South-central Mediterranean Sea) - Di BONA, GABRIELE; BERLINO, MANUEL; SARÀ, GIANLUCA; MANGANO, MARIA CRISTINA (Mediterranean Marine Science, 2025)
Trawling along continental shelves causes severe disruptions to benthic communities by altering sedimentary compositions and increasing species mortality, thus favoring opportunistic species over long-living, ecologically important ones. This study was carried out in the southern Strait of Sicily, a highly exploited fishing ground, using a trait-based ecosystem approach to assess the impacts of trawling in sandy and muddy sediments. The intensity of fishing here, measured by the swept area ratio (0.36-37.37), has exhibited a gradient from coastline to offshore, peaking along the eastern continental shelf. Surveys, being part of studies, captured 8191 individuals from 103 species (70% demersal). Demersal species’ density decreased with fishing intensity but increased with temperature, while benthic species density correlated positively with temperature and chlorophyll concentration. Taxonomic diversity was unaffected by fishing intensity but driven by chlorophyll, negatively for demersal species and positively for benthic diversity. Functional diversity showed no significant variation. Multivariate analysis explained limited variance in taxonomic and functional composition, highlighting the homogenization of benthic communities due to chronic trawling and bathymetric variation. Assemblages in this study reflected long-term exploitation, favoring opportunistic species and masking functional adaptations to fishing and environmental gradients. These findings emphasize the subtle yet significant impacts of chronic disturbances on benthic ecosystems, underscoring the value of trait-based analyses for assessing ecological responses in highly exploited zones.